Tingkat Motivasi Latihan Bola Basket Pada Unit Kegiatan Mahasiswa Bola Basket Universitas Djuanda: Tingkat Motivasi Latihan Bola Basket Pada Unit Kegiatan Mahasiswa Bola Basket Universitas Djuanda - Yudho, Firdaus Hendry Prabowo; Nugroho, Aditia (INSPIREE: Indonesian Sport Innovation Review, 2021)
The purpose of the study This study aims to determine how high the level of training motivation of athletes when carrying out training. The background of this research is the inconsistency level of achievement shown by the Basketball Student Activity Unit, Djuanda University, Bogor. Materials and methods. This research was conducted with a quantitative approach, through descriptive methods using a survey method of the basketball team members consisting of 20 people. Data in the form of questionnaire values ​​on the Likert scale were processed using simple statistics SPSS Version 26 to determine the value of descriptive statistics as the final result of the study. Results. The results showed that the level of motivation of athletes who took part in training at the basketball Student Activity Unit (UKM) at Djuanda University, Bogor was in the moderate majority. This result is based on the consideration that the highest frequency is in the medium criteria of 40%. Motivation of athletes in the criteria is very high by 5%, 20% high, 20% less and 15% very less. Conclusions. The percentage of motivation revealed from this study was dominated by the medium category, with a percentage that was less than the high percentage 25% <35%. This can be taken into consideration to be able to evaluate the psychological training program and mental training of the basketball club athletes for better achievement.